2018
DOI: 10.6002/ect.2017.0017
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Mycophenolate mofetil is a first-line drug after organ transplant, but there are differences in metabolism of mycophenolate mofetil among individuals. The UDP glucuronosyltransferase enzyme is the key metabolic enzyme for mycophenolate mofetil, and UGT1A8 gene polymorphisms may affect the elimination of mycophenolate mofetil in patients. Here, we conducted an in vitro study to explore the relation between UGT1A8 gene polymorphisms and mycophenolate mofetil metabolism. Materials and Methods: Five mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There are no reports to date regarding UGT1A8 in ovarian cancer. There is one study of recombinant human UDP-glucuronosyltransferases (UGTs), including UGT1A1, but Zhou [60] found that UGT1A8 gene polymorphisms can affect the activity of the UDP glucuronosyltransferase enzyme, which may influence the elimination of mycophenolate mofetil in different patients. The 6 CNV-driven genes identified in the present study may be potential markers for ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports to date regarding UGT1A8 in ovarian cancer. There is one study of recombinant human UDP-glucuronosyltransferases (UGTs), including UGT1A1, but Zhou [60] found that UGT1A8 gene polymorphisms can affect the activity of the UDP glucuronosyltransferase enzyme, which may influence the elimination of mycophenolate mofetil in different patients. The 6 CNV-driven genes identified in the present study may be potential markers for ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For overlapped delta-shaped anastomosis, disarticulation and anastomosis do not need to be performed extracorporeally; therefore, a smaller portion of the intestines is required to be freed laparoscopically. In addition, this anastomosis technique does not limit the location of the incision, so smaller Pfannenstiel incisions can be used using this technique; it is less invasive, gives better cosmetic results and can decrease the incidence of incisional hernias 13,14. Above all, this procedure is associated with fewer complaints of postoperative pain and leads to earlier postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The length of incision was shorter in the IDA group than in the EA group ( P < 0.001); however, we think the difference of 1 cm in length is not very significant clinically. Additionally, this technique of anastomosis does not limit the location of the incision; hence, we can apply the Pfannenstiel incision in patients in the IDA group, since it is less invasive, has better cosmesis and decreases the incidence of incisional hernia [15, 16]. Above all, it is associated with less post-operative pain.…”
Section: Discussionmentioning
confidence: 99%